Co-designing reform-based online inquiry learning environments as a situated approach to teachers' professional development. Issue 4 (2nd October 2017) - Kyza, Eleni A.; Nicolaidou, Iolie
Abstract: This study examined the contribution of a co-design approach to science teachers' situated professional development, and explored its effect on student learning and motivation. Study participants were three science teachers who were members of a co-design team; one of the teachers enacted the designed learning environment with her 11th grade, non-science major students. Data were collected from 31 design meetings over two years, teacher interviews, and from pre-post student learning and motivation assessments. Findings indicated that the co-design approach addressed teachers' reform-based professional development needs, had greater impact on the enacting teacher, and met the enacting students' learning and motivation needs. The findings talk to the potential of co-design as a successful approach for teachers' reform-based, situated professional development.